Speaking of Irony: Bournonville, Kierkegaard, H.C. Andersen and the Heibergs - Roth, Colin (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
Colin Roth: Speaking of Irony   The purpose of this article is to draw attention to the ironic and satiric intent of a speech that the choreographer, August Bournonville, made in October 1861, and, in exploring its references, to shed light on the friendship-circles to which he belonged. Extensive quotations from contemporary documents – diaries, letters and published works – are employed to establish the character and concerns of the players, some of whom may not be familiar to specialists in the different disciplines represented here.